A soldier's place [videorecording] - Gould, Tom; Levine, Michael. Kirk, David; Maclear, Michael (A%E Home Video, 1995)
A documentary on the use of United Nations Armed forces to mediate international disputes. Incorporates footage and interviews with key international policy makers.